2020
DOI: 10.1038/s42003-020-01346-w
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals orchestrate reprogramming with hierarchical activation of master transcription factors primed by endogenous Sox17 activation

Abstract: Mouse somatic cells can be chemically reprogrammed into pluripotent stem cells (CiPSCs) through an intermediate extraembryonic endoderm (XEN)-like state. However, it is elusive how the chemicals orchestrate the cell fate alteration. In this study, we analyze molecular dynamics in chemical reprogramming from fibroblasts to a XEN-like state. We find that Sox17 is initially activated by the chemical cocktails, and XEN cell fate specialization is subsequently mediated by Sox17 activated expression of other XEN mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…To investigate how chemical compounds alter cell fate, we previously studied the chemical reprogramming process from mouse embryonic fibroblasts (MEFs) to XEN-like cells. The study revealed a hierarchical activation of XEN cell master TFs primed by Sox17 and the different roles of essential chemicals during the process (Yang et al, 2020). In parallel to that study, we measured the global gene expression profiles by RNA sequencing during reprogramming.…”
Section: Chemical Reprogramming Cocktails Initially Activated the Exp...mentioning
confidence: 92%
See 4 more Smart Citations
“…To investigate how chemical compounds alter cell fate, we previously studied the chemical reprogramming process from mouse embryonic fibroblasts (MEFs) to XEN-like cells. The study revealed a hierarchical activation of XEN cell master TFs primed by Sox17 and the different roles of essential chemicals during the process (Yang et al, 2020). In parallel to that study, we measured the global gene expression profiles by RNA sequencing during reprogramming.…”
Section: Chemical Reprogramming Cocktails Initially Activated the Exp...mentioning
confidence: 92%
“…The data used in the RNA-Seq analysis was combined with our previous data (Yang et al, 2020), and we additionally performed RNA-Seq on the C6F5UE treatment group. Gene expression levels were normalized as log 2 (FPKM+1) in all bulk RNA-Seq data.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 3 more Smart Citations